Centrifugal microfluidic platforms: advanced unit operations and applications. (2nd June 2015) - Strohmeier, O.; Keller, M.; Schwemmer, F.; Zehnle, S.; Mark, D.; von Stetten, F.; Zengerle, R.; Paust, N.
Abstract : Review on miniaturization, integration, and automation of laboratory processes within centrifugal microfluidic platforms. For efficient implementation of applications, building blocks are categorized into unit operations and process chains. Abstract : Centrifugal microfluidics has evolved into a mature technology. Several major diagnostic companies either have products on the market or are currently evaluating centrifugal microfluidics for product development. The fields of application are widespread and include clinical chemistry, immunodiagnostics and protein analysis, cell handling, molecular diagnostics, as well as food, water, and soil analysis. Nevertheless, new fluidic functions and applications that expand the possibilities of centrifugal microfluidics are being introduced at a high pace. In this review, we first present an up-to-date comprehensive overview of centrifugal microfluidic unit operations. Then, we introduce the term "process chain" to review how these unit operations can be combined for the automation of laboratory workflows. Such aggregation of basic functionalities enables efficient fluidic design at a higher level of integration. Furthermore, we analyze how novel, ground-breaking unit operations may foster the integration of more complex applications. Among these are the storage of pneumatic energy to realize complex switching sequences or to pump liquids radially inward, as well as the complete pre-storage and release of reagents. In this context, centrifugal microfluidics provides major advantages over other microfluidic actuation principles: the pulse-free inertial liquid propulsion provided by centrifugal microfluidics allows for closed fluidic systems that are free of any interfaces to external pumps. Processed volumes are easily scalable from nanoliters to milliliters. Volume forces can be adjusted by rotation and thus, even for very small volumes, surface forces may easily be overcome in the centrifugal gravity field which enables the efficient separation of nanoliter volumes from channels, chambers or sensor matrixes as well as the removal of any disturbing bubbles. In summary, centrifugal microfluidics takes advantage of a comprehensive set of fluidic unit operations such as liquid transport, metering, mixing and valving. The available unit operations cover the entire range of automated liquid handling requirements and enable efficient miniaturization, parallelization, and integration of assays.